Closed-Loop Sustainability: Leveraging Canteen Food Waste for Maggot Cultivation and Decorative Fish Feeding in an Automotive Spare Parts Manufacturing Facility in Bekasi, Indonesia - Nugroho, Adi (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
An automotive spare parts manufacturing plant in Bekasi Regency, Indonesia, has created a closed-loop sustainability project to address the essential issue of food waste management. With a canteen that serves 3,500 employees every day, the facility creates a lot of food waste, which has traditionally caused environmental and financial problems. The activity-integrated approach highlights the potential for novel waste management strategies to promote sustainability in industrial settings. The research frequently treats waste management and resource production (such as decorative fish ponds) as distinct domains, with a scarcity of studies focusing on sustainability practices within facilities catering to large employee populations with internal systems (such as canteens) that generate significant waste. As a result, it closes the gap by offering a case study of how an internal waste stream. The major goal is to create and execute a closed-loop system that converts food waste into a useful resource, maggots, for feeding decorative fish. Similarly, examine the economic benefits of eliminating the need for commercially supplied fish feed, as well as the environmental impact of decreasing food waste through an integrated waste management approach. This study employs a case study technique to analyze the deployment and consequences of a closed-loop sustainability system at an automotive spare parts manufacturing facility. The method provides for a thorough analysis of the procedures, obstacles and triumphs that come with repurposing food waste for maggot cultivation and fish feeding. The adoption of the closed-loop system successfully diverted a significant volume of food waste from the canteen, decreasing the environmental impact of typical trash disposal methods. Furthermore, the project resulted in significant cost savings by eliminating the need to buy commercial fish feed. As a result, the closed-loop technology helped to reduce the facilities overall carbon footprint by reducing waste and the requirement for externally supplied feed ingredients, which generally demand significant resources to produce and deliver. The discovery establishes a feasible approach for deploying closed-loop sustainability systems in industrial settings. It demonstrates how merging waste management and resource generation can improve sustainability while reducing operational expenses. Furthermore, demonstrated financial benefits, such as cost savings and potential profitability, can pique the interest of industry stakeholders for sustainable and economically viable solutions. The study also emphasizes the environmental benefits of reducing waste and reducing reliance on commercially produced feed, which contributes to a lower carbon footprint and reduces the environmental impact of manufacturing processes. Finally, the effort contributes to the company's CSR profile, demonstrating a commitment to environmental stewardship and appropriate resource management, which improves the companies reputation and employee morale.